Traditional and new composite endpoints in heart failure clinical trials: facilitating comprehensive efficacy assessments and improving trial efficiency. (12th April 2016) - Anker, Stefan D.; Schroeder, Stefan; Atar, Dan; Bax, Jeroen J.; Ceconi, Claudio; Cowie, Martin R.; Crisp, Adam; Dominjon, Fabienne; Ford, Ian; Ghofrani, Hossein‐Ardeschir; Gropper, Savion; Hindricks, Gerhard; et al.
Abstract: Composite endpoints are commonly used as the primary measure of efficacy in heart failure clinical trials to assess the overall treatment effect and to increase the efficiency of trials. Clinical trials still must enrol large numbers of patients to accrue a sufficient number of outcome events and have adequate power to draw conclusions about the efficacy and safety of new treatments for heart failure. Additionally, the societal and health system perspectives on heart failure have raised interest in ascertaining the effects of therapy on outcomes such as repeat hospitalization and the patient's burden of disease. Thus, novel methods for using composite endpoints in clinical trials (e.g. clinical status composite endpoints, recurrent event analyses) are being applied in current and planned trials. Endpoints that measure functional status or reflect the patient experience are important but used cautiously because heart failure treatments may improve function yet have adverse effects on mortality. This paper discusses the use of traditional and new composite endpoints, identifies qualities of robust composites, and outlines opportunities for future research.